The 'science' of superiority: Africa and scholarly colonial assumptions. Issue 4 (2nd October 2018) - Friedman, Steven
ABSTRACT: The use of 'neopatrimonialism' as a category in mainstream scholarship on African polities and economies is ubiquitous. A critique by Thandika Mkandawire has shown that the 'neopatrimonial school' is devoid of conceptual coherence and analytical power – it is an expression of a prejudice, not a useful tool for research and analysis. The article endorses Mkandawire's view but points out that this is by no means the only example of its kind. On the contrary, the use of categories which assume the superiority of societies in the global North over those in Africa is widespread. The article illustrates this by discussing and criticising two others, the 'democratic consolidation' paradigm and the 'failed state' framework. It argues that all three shape assumptions by scholars in Africa as well as outside it which obstruct concrete analysis. A critique of these paradigms is thus essential to the development of scholarship on and about Africa.